2012
DOI: 10.1007/s00422-012-0489-3
|View full text |Cite
|
Sign up to set email alerts
|

Developing structural constraints on connectivity for biologically embedded neural networks

Abstract: In this article, we analyse under which conditions an abstract model of connectivity could actually be embedded geometrically in a mammalian brain. To this end, we adopt and extend a method from circuit design called Rent's Rule to the highly branching structure of cortical connections. Adding on recent approaches, we introduce the concept of a limiting Rent characteristic that captures the geometrical constraints of a cortical substrate on connectivity. We derive this limit for the mammalian neocortex, findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…However, few models have taken the small-world structure of neural ensembles into consideration. The recently developed methods have provided powerful tools for studying the functional connectivity property of brain networks (Sporns and Zwi 2004;Eldawlatly et al 2009;Partzsch and Schüffny 2012;Leergaard et al 2012). Most of them demonstrated that biological networks presented small-world properties, observed not only in large neural networks with each node representing a cortical area (Sporns and Zwi 2004;Bassett and Bullmore 2006;Kaiser 2008), but also in the local neural networks recorded with microelectrode arrays (Yu et al 2008;Gerhard et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, few models have taken the small-world structure of neural ensembles into consideration. The recently developed methods have provided powerful tools for studying the functional connectivity property of brain networks (Sporns and Zwi 2004;Eldawlatly et al 2009;Partzsch and Schüffny 2012;Leergaard et al 2012). Most of them demonstrated that biological networks presented small-world properties, observed not only in large neural networks with each node representing a cortical area (Sporns and Zwi 2004;Bassett and Bullmore 2006;Kaiser 2008), but also in the local neural networks recorded with microelectrode arrays (Yu et al 2008;Gerhard et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For each network, there is an empirical discrete function P  =  P c ( B ), called Rent characteristic 6, 7 , which directly relates the average number of nodes B for a topological partition of the network to the average number of edges P connecting different modules of the partition. We are interested in determining Region I where Rent characteristic fits well to Rent’s rule.…”
Section: Validating Rent’s Rulementioning
confidence: 99%
“…It relates the average number of external connections or pins on a module and the average number of blocks within the module for partitions of computer logic graphs 2 . Besides its extensive application in Circuit Design at all scales, from SSI to GSI passing through VLSI, Rent’s rule has been used to study the interconnection complexity of biological networks 3–6 , as well some benchmark models and technological networks 79 . At origin, given a logic circuit, the relationship between the average number of blocks or cells B in a module in a given partition and the average number of pins P connecting each module with the others iswhere k is the average number of pins per logic block (also called Rent coefficient ) and p is the Rent exponent describing proportionality in a log-log scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations